Socio-Economic Status of Widows - Padmanabhan, K (Kochappi), 1944- (New Delhi : Serials Publications, 2006)
Study of Mudaliar community of Tamil Nadu, India.
Includes bibliographical references (p. [237]-239).
Keywords: Widows -- India -- Tamil Nadu -- Social conditions; Widows -- India -- Tamil Nadu -- Economic conditions; Mudaliars -- Social conditions; Mudaliars -- Economic conditions